2003
DOI: 10.1186/1471-2091-4-17
|View full text |Cite
|
Sign up to set email alerts
|

A novel form of the membrane protein CD147 that contains an extra Ig-like domain and interacts homophilically

Abstract: BackgroundCD147 is a broadly distributed integral membrane glycoprotein with two Ig-like domains implicated in a wide range of functions. It is associated at the cell surface with the monocarboxylate transporters MCT1 and 4 but interactions of the extracellular region have not been characterised.ResultsWe report the characterisation of a form of CD147 with an additional membrane-distal Ig-like domain. In contrast to the two domain form, this three domain form of CD147 interacts homophilically. Surface plasmon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…This result implies that rBSG associates with an unknown membrane receptor prior to being internalized into the cell. Previous reports have suggested that basigin-2 can function as the membrane receptor for soluble basigin protein, but attempts to directly test this hypothesis have not demonstrated this ability (20,31). We tested this hypothesis by repeating the basigin immunoprecipitations from labeled HESC fractions, followed by immunoblotting with neutravidin-HRP to detect the transfer of the biotin label from the SBED-labeled rBSG to basigin-2 in the membrane fraction.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…This result implies that rBSG associates with an unknown membrane receptor prior to being internalized into the cell. Previous reports have suggested that basigin-2 can function as the membrane receptor for soluble basigin protein, but attempts to directly test this hypothesis have not demonstrated this ability (20,31). We tested this hypothesis by repeating the basigin immunoprecipitations from labeled HESC fractions, followed by immunoblotting with neutravidin-HRP to detect the transfer of the biotin label from the SBED-labeled rBSG to basigin-2 in the membrane fraction.…”
Section: Resultsmentioning
confidence: 96%
“…Together, the evidence suggests that basigin expressed on the surface of cells can function as a counter-receptor for basigin expressed on separate cells or for soluble glycosylated forms of basigin. Nevertheless, previous attempts to demonstrate such a direct interaction between basigin molecules on separate cells or between basigin proteins in solution have not been successful (20,31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Basigin‐2 (NM_198589) is a major isoform of basigin, and it is ubiquitously expressed. While basigin‐1 transcript (NM_001728), with a third immunoglobulin domain (Ig0), is only expressed specifically in the retinal photoreceptors 19, 26, 27. Basigin‐1, associating with a protein secreted from rods, being named as rod‐derived cone viability factor (RdCVF) and glucose transporter (Glut)‐1, form a complex at the cone surface to increase glucose uptake and promotes cone survival 28, 29.…”
Section: Discussionmentioning
confidence: 99%